(untitled) (Eurasian Journal of Philology Science and Education, 2022)
This article is devoted to a comparative analysis of the grammatical characteristics of the Russian, English and Polish languages with a projection on the perception of their carriers. Grammems are taken as the basis of the factual material, in which the mental characteristics of the people are reflected to one degree or another. For research of actual material the complex of scientific methods was used, in particular the method of semantic analysis, the comparative method, and the method of cognitive analysis. The theoretical significance of the study lies in obtaining comprehensive data on the grammatical properties of European languages in the context of their similarities and differences. The obtained gnoseological material should be used in teaching practice. The practical focus of the research is connected with the thesaurus-oriented teaching methodology, which contributes to a more conscious assimilation of grammatical facts and the formation of a student as a multilingual personality. The results of the study indicate a significant unification of grammatical semantics in Russian, Polish and English, which projects a number of mental traits of native speakers of these languages to be common. At the same time the different ways of cultural and historical development of people stipulated distinction of a number of grammatical descriptions, foremost in the plan of expression. Efficiency of an offer methodology confirms the conducted pedagogical experiment